(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The purpose of this study is to evaluate the phenotypic characteristics and typification of Creole goats in five localities of the Ayacucho region in south-central Peru. Materials and Methods: Data from 149 goats (25 males and 124 females) were collected, excluding animals under 2 years of age, pregnant, and sick. Seven qualitative characteristics and 11 zometric measurements were evaluated, and then 9 zometric indices were estimated. Results: In the region, goats with composite colors predominated (76.50%). Additionally, supernumerary (24.20%) and divergent teats (22.60%) were observed in females, while males exhibited a scrotal bifurcation (32.00%). The origin of the flock had a significant effect (p < 0.05) on body measurements, as well as on pelvic index, transverse pelvic index, longitudinal pelvic index, compactness index, and load cannon bone index, except for body index (BOI), proportionality index, dactyl thorax index (DTI), and relative cannon bone thickness index (p > 0.05). In the Ayacucho region, there is a predominance of light animals (57.72%) with a significant DTI (p < 0.05) among the populations, including goats with good balance and capable of walking long distances. Furthermore, there are compact animals (47.65%) with a significant BOI (p < 0.05) among the flock populations, which animals are of the biotype of meat. Conversely, the strongest positive correlation (r = 0.89) was discovered between chest girth and body weight. Conclusion: In the Ayacucho region, there are various creole goat biotypes range from light to very compact heavy goats, with a predominance of meat biotype animals, as well as a marked size dimorphism between localities of origin. Adv. Vet. Anim. Res., 11(2): 494-502, June 2024 http://doi.org/10.5455/javar.2024.k799